“Care for another” in everyday life and professional nursing practice – experience of nursing students - Dobrowolska, Beata; Ślusarska, Barbara; Zarzycka, Danuta; Cuber, Tomasz (Polish Journal of Public Health, 2010)
Introduction. The value of care for another belongs to the oldest and most important goods of medicine, especially nursing. The development of a human natural tendency to care for someone and getting knowledge and skills how to perform it are the aims of nursing education. Aim. The aim of the article was to analyse nursing students’ statements about the realisation of care for another person in everyday life and vocational practice and to evaluate the evolution of care performance which was pointed out by students. Material and methods. The qualitative analysis of data collected among the Lublin University of Medicine students of nursing from the first and the last years was made. The data were collected in 2008/2009 academic year. Totally 56 students participated in the study. Results and conclusions. Family is the source of caring attitude of students. The realisation of care in everyday life mostly concerns the close members of family. The forms of care in both groups comprise nursing activities and caring interpersonal communication as a “tool” of compassion. The analysis of care activities in the clinical reality showed the professionalization of the undertaken activities.